IMPLEMENTATION OF YOUTUBE MEDIA IN THE DIGITAL ERA TO IMPROVE THE QUALITY OF QUR'AN HADITH LEARNING IN MADRASAH - Sayuti, Lalu; Supratman, Supratman; Yaldi, Yusri; Salim, Agus (INTIHA: Islamic Education Journal, 2024)
Digital era learning media can enhance quality and facilitate teachers and students in teaching and learning activities. YouTube is a very popular online video-sharing platform. Users can watch, upload, and share videos easily. Its content is highly diverse, ranging from Islamic film clips, Qur'an recitations, to Qur'an educational videos and tutorials. Currently owned by Google, YouTube is the second most popular site in the world. YouTube can provide learning to humans in the form of edited videos on the application. It helps students understand complex subject matter, bridge understanding gaps, and improve learning effectiveness. This application is highly favored by teachers and students because the videos presented are well-structured and can even deliver learning in a short time. This study employs library research, an approach involving in-depth analysis of literature. It discusses the implementation of YouTube in Qur'an Hadith learning in Madrasah, including how to use the application, its advantages and disadvantages, and its goal for teachers and students to use this media effectively. Thus, this study aims to provide more accurate information, relevance, and how to utilize YouTube in Qur'an and Hadith learning effectively. Therefore, it is necessary to integrate technology appropriately and effectively in learning, as well as develop teacher competencies in managing technology-based learning.